Synthesis and photovoltaic properties of new Ru(II) complexes for dye-sensitized solar cells - Dayan, Osman; Ozdemir, Namik; Yakuphanoğlu, Fahrettin; Serbetci, Zafer; Bilici, Ali; Cetinkaya, Bekir; Tercan, Melek (Springer, 2018)
Two groups Ru(II) complexes, (1A-C and 2A) (A-C = 2,6-bis(2-benzimidazolyl)pyridines, bbpy, with various substituents at 2-, 5-, and 6-positions) have been prepared and applied for dye-sensitized solar cells (DSSC). The compounds were characterized by various techniques. The optical and electrical properties of sensitizers were investigated with UV-Vis absorption spectroscopy and cyclic voltammetry. High power conversion efficiencies up to 5.16%, have been achieved with 2Ae. Current-voltage characteristics of DSSCs clearly affected by the changing of the ligands at sensitizers. Additionally, computational studies show that locations of frontier molecular orbitals are significantly important for power-conversion efficiencies in DSSCs.
Keywords: Effective Core Potentials; Charge-Transfer Sensitizers; Pyridine-Based Tridentate; Ruthenium(Ii) Complexes; Molecular Calculations; Transfer Hydrogenation; Polypyridyl Complexes; Catalytic-Activity; Ancillary Ligands; 2,6-bis(Benzimidazol-2-Yl)Pyridine